Correlation between mean arterial pressure (MAP) and brain saturation (RSO2) in patients undergoing moderate hypotensive anesthesia for septo- and rhinoplastic surgery - Kraleva, Silvana; Shirgoska, Biljana; Trajkova, Radmila; Klisheska Ilcevska, Ivana (Институт за јавно здравје на Република Македонија = Institute of public health of Republic of Macedonia, 2019)
Hypotensive anesthesia is such anesthetic technique where during general anesthesia the patient‘s mean arterial pressure is decreased by more than 20% of its preoperative value. Motivation: To prevent the occurrence of brain hypoxia during hypotensive anesthesia in patients undergoing septo- and rhinoplastic surgery. Aims: To determine the average values of brain saturation in awaken patients; to find the correlation between the mean arterial pressure and brain saturation during moderate hypotension, and to analyze the adverse reactions postoperatively. Materials and methods: Twenty (ASA 1) patients, anaesthetised in moderate hypotensive general anesthesia with Remifentanyl and Sevoflurane were enrolled in the study. They were observed at five times interval (T1-5): MAP, HR and rSO2, and a correlation between the parameters was determined. Results: A moderate hypotension was achieved in T4 (MAP = 69.05 ± 7.09). The average baseline values of brain saturation from 73.30 ± 5.44% to the left, 75.30 ± 5.18% to the right brain hemisphere were obtained. The curve of brain saturation had an upward trend, a peak that coincided with an introduction to anesthesia, in a further course with a downward trend. We found a mild to moderate positive correlation between MAP and rSO2 during hypotensive anesthesia, but throughout the entire period there was a higher rSO2 than the basal initial value. Conclusion: Moderate hypotension and stable mean arterial pressure (MAP) contribute to stable brain saturation (rSO2).
Kорелација помеѓу средниот артериски притисок (МАР) и мозочната сатурација (RSO2) кај пациенти подложени на хипотензивна општа анестезија при септо- и ринопластика